2015
DOI: 10.4049/jimmunol.1401303
|View full text |Cite
|
Sign up to set email alerts
|

Demethylation of the RORC2 and IL17A in Human CD4+ T Lymphocytes Defines Th17 Origin of Nonclassic Th1 Cells

Abstract: Th17-derived Th1 lymphocytes, termed nonclassic, differ from classic Th1 cells because of the presence of retinoic acid orphan receptor (ROR)C2 and the surface expression of CD161 and CCR6. We demonstrate in this article that nonclassic Th1 cells, like Th17 cells, have a marked RORC2 and IL17A demethylation, whereas classic Th1 cells exhibit a complete methylation of these genes. The analysis of RORC2 DNA methylation in the CD4+CD161+ and CD4+CD161− naive Th subsets from umbilical cord blood surprisingly revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0
4

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 30 publications
4
50
0
4
Order By: Relevance
“…These cells may derive directly from naïve T cells in a RORgt-dependent fashion or from T H 17 cells that convert to T H 1 Ã under the influence of IL-12, TNF-a, and/or IL-1b. The latter possibility is consistent with the finding that in T H 1 Ã cells, like in T H 17 cells, RORC2 and IL17A are demethylated (Mazzoni et al 2015).…”
Section: Heterogeneity Of Human Cd4 T Cellssupporting
confidence: 85%
“…These cells may derive directly from naïve T cells in a RORgt-dependent fashion or from T H 17 cells that convert to T H 1 Ã under the influence of IL-12, TNF-a, and/or IL-1b. The latter possibility is consistent with the finding that in T H 1 Ã cells, like in T H 17 cells, RORC2 and IL17A are demethylated (Mazzoni et al 2015).…”
Section: Heterogeneity Of Human Cd4 T Cellssupporting
confidence: 85%
“…This protocol has been widely used to reveal the cytokine production capabilities of T cells, including studies on MS (Mazzoni et al, 2015). Cells were incubated with antibodies specific for surface markers for 20 min at 4 °C before washing.…”
Section: Methodsmentioning
confidence: 99%
“…Potentially pathogenic CCR6 + Th subsets that do not secrete IL-17A includes non-classic or non-conventional Th1 cells, a population originally characterised by the expression of CD161 and/or CCR6 (Acosta-Rodriguez et al, 2007, Becattini et al, 2015, Maggi et al, 2010, Maggi et al, 2012). Epigenetic analysis of these cells showed that they most likely originate from Th17 cells, but have lost their ability to produce IL-17A (Mazzoni et al, 2015), with studies in juvenile idiopathic arthritis demonstrating their presence in both the blood and synovial fluid. In this study we explored the association of CCR6 with the pathogenic cytokines IL-17, IFNγ and GM-CSF in CD4 + T cells and in particular their association with MS. We demonstrate that the dominant CSF CD4 + T cell subset is not composed of IL-17-secreting T cells, but non-classic/non-conventional Th1 cells as well as GM-CSF-only-secreting Th cells.…”
Section: Introductionmentioning
confidence: 99%
“…A second explanation for the trend towards higher RORγτ expression in CD4+CCR6+ T cells and intracellular IL-17 production despite hypermethylation at RORC regions in dcSSc is that in our assay, DNA from total PBMCs due to small sample volumes of dcSSc patients and HC was taken to analyze methylation levels at RORC1 , RORC2 , FOXP3 , STAT3, and STAT5A regions, but not from isolated T-cell subsets. Recently, it has been shown that RORC2 is differentially methylated in classic CD4+CD161-CCR6-IFNγ+ Th1 cells, and transiently in Th17/Th1 (CD4+CD161+CCR6+IL-17A+IFNγ+) cells and nonclassic CD4+CD161+CCR6+IFNγ+ Th1 cells [57]. Thus, hypermethylation at RORC regions may result rather from other Th cell subpopulations, such as Th1 or Th2, than from the relatively small peripheral Th17 subpopulation.…”
Section: Discussionmentioning
confidence: 99%